American film history selected readings, 1960 to the present - Lucia, Cynthia A. Barto (Cynthia Anne Barto); Grundmann, Roy 1963-; Simon, Art (John Wiley & Sons Inc., 2016)
"Covers a broad range of topics ranging from the early 1900s Nickelodeon, silent film and its iconic figures such as Charlie Chaplin, to the coming of sound, genres, studio moguls, and the Cold War blacklist"--Provided by publisher.